Farming with alternative pollinators - Paparella, Antonio; Petsakos, Athanasios; Davis, Kristin E.; Song, Chun (International Food Policy Research Institute, 2025)
The relationship between plants and pollinators is widely recognized as one of the most significant forms of ecological interactions [1]. Without pollinators, numerous plant species could not reproduce. Additionally, many animals rely on plants for essential resources such as pollen and nectar. This relationship is remarkably frequent in nature, with an estimated 87% of flowering plants pollinating through animal interaction [2]. Consequently, pollinators are also essential for humanity, especially for their contribution to food security since they are necessary to produce various crop commodities [3]. The production of medicines, biofuels, and construction materials relies, to some extent, on the pollination carried out by animals. Finally, the livelihood of many people is based on beekeeping and honey gathering, which are ancient activities yet still important in many rural communities [3]. Pollination is a recognized ecosystem service, and its economic value has been assessed numerous times [4], [5], [6]. However, we witness a rapid biodiversity decline in terms of wild pollinators, which is caused by human activities [7]. Among the factors leading to this decline, the intensive and improper use of agrochemicals is arguably the most severe [8]. For instance, the practice of seed coating with systemic pesticides (such as Imidacloprid) affects the nectar and pollen, causing a potential threat to pollinators [9], [10]. Habitat fragmentation, loss, and degradation are also important drivers of the decline of wild pollinators. These can be caused by urbanization, removal of “waste places” like hedgerows and field margins, and (over)grazing and early cutting of hay meadows [8]. Climate change is an additional risk, interrupting the timely synchronization of plant-pollinator interactions